A combination of tapered fibre and polarization controller in generating highly stable and tunable dual-wavelength C-band laser. Issue 7 (12th April 2017) - Ahmad, H.; Faruki, M. J.; Razak, M. Z. A.; Jaddoa, M. F.; Azzuhri, S. R.; Rahman, M. T.; Ismail, M. F.
Abstract: This paper demonstrates the use of a tapered fibre in generating a highly stable and tunable dual-wavelength fibre laser. By unique arrangement of polarization controller, adjustable spacing range between 0.94 and 3.32 nm and side mode suppression ratio (SMSR) up to 50 dB were recorded. The results were achieved at laser pump power of 94.7 mW. The inter-modal interference is achieved through the use of a non-adiabatic tapered fibre, made by a systematic flame brushing technique. The tapered fibre suppresses the mode competition in the 3-m erbium-doped fibre (EDF) gain medium. Over 60 min, the laser exhibited very high stability with acceptable peak power and SMSR. The proposed EDF laser operates from 1556.71 to 1562.13 nm range.